2010
DOI: 10.1080/01919512.2010.500900
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Oxidation Treatment of Drinking Water: Part II. Turbidity, Particles and Organics Removal from Lake Huron Water

Abstract: Pre-coagulation ozonation has been reported to be effective in drinking water treatment processes. Limited data are available on the impact of advanced oxidation processes (AOPs) on Lake Huron water which serves as a primary source of drinking water for many communities around the Great Lakes region. Impact of ozone/hydrogen peroxide based AOP on Lake Huron water was studied. The results show that AOPs can achieve higher particles removal in finished water and deliver improved filtered water turbidity compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…3d). These experiments implied that the ozonation process could effectively oxidize unsaturated organic compounds into saturated compounds and eliminate the UV 254 index (Andreozzi et al, 1999), while its mineralization was limited evidenced by a lower decrease of the DOC index, although some unsaturated compounds had changed into saturated ones (Rahman et al, 2010;Can and Ç akir, 2010), which might cause an increase in genotoxicity due to the formation of toxic oxidation by-products (Stalter et al, 2010). Reungoat et al (2010) investigated the relationship between the removal of micropollutants and biological effects during ozone-activated carbon processes, and found that the mixture of oxidation by-products had less toxic potential than the mixture of parent compounds.…”
Section: Proposal Of Toxicity Assessment Indexmentioning
confidence: 99%
“…3d). These experiments implied that the ozonation process could effectively oxidize unsaturated organic compounds into saturated compounds and eliminate the UV 254 index (Andreozzi et al, 1999), while its mineralization was limited evidenced by a lower decrease of the DOC index, although some unsaturated compounds had changed into saturated ones (Rahman et al, 2010;Can and Ç akir, 2010), which might cause an increase in genotoxicity due to the formation of toxic oxidation by-products (Stalter et al, 2010). Reungoat et al (2010) investigated the relationship between the removal of micropollutants and biological effects during ozone-activated carbon processes, and found that the mixture of oxidation by-products had less toxic potential than the mixture of parent compounds.…”
Section: Proposal Of Toxicity Assessment Indexmentioning
confidence: 99%
“…In relation to the presence of organic compounds in the water, a lower concentration (but not very significant) of O 3 was observed in tap water. The presence of organic matter can cause a severe reduction of O 3 in water [42][43][44], due to the rapid action of this agent with the aqueous compounds. However, it is precisely for this reason that O 3 (in its gas form) is widely used in the treatment of wastewater [40,45,46]-for example, reacting with the dirtiness by the direct action of molecular O 3 or by indirect reaction of the radical OH − [32,46].…”
Section: O 3 Stability In Watermentioning
confidence: 99%
“…Mechanisms by which the ozonation process can influence the coagulation process and consequently improved the water turbidity are as follows [44]:…”
Section: Effect Of the System On Turbidity Reductionmentioning
confidence: 99%